An adaptive large neighborhood search heuristic for the sectoring-arc routing problem - Nunes, Ana Catarina; Cortinhal, M.J.; Mourão, Maria Cândida (EURO-INFORMS XXVI - 26th European Conference on Operational Research, 2013)
The sectoring-arc routing problem involves partitioning one area into sectors, within a time-limit and building arc routing trips per sector, within the vehicles capacity. Among its several real world applications lies the refuse collection. In the refuse collection problem, the aim is to design routes that minimize the total routing cost but taking into account desirable features for the sectors, such as balancing, compactness and contiguity. We propose an adaptive large neighborhood search heuristic. The performance of the algorithm is evaluated over a set of benchmark problems.